(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article provides scientific evidence of aerobics classes and its comprehensive effect on the body of female students of pedagogical universities. Currently, the choice and application of physical exercises is carried out taking into account several main tasks. To solve these basic tasks, aerobics has a wide range of exercises. These exercises are distinguished by strictly specified conditions of performance, which include a certain rhythm of movements, the sequence of building combinations of individual exercises, the direction of the impact on the body of the student.